MANAJEMEN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN MINAT BELAJAR SISWA DI SMA NEGERI 2 KOTA TEBING TINGGI PROVINSI SUMATERA UTARA - Nurwilda Safitri (Hijri, 2017)
This study aims to find out the management learning Islamic religious education in improving interest in learning in high school students 2 City Tebing Tinggi. This research is a qualitative research. Data collection in this research is done by observation technique, interview and document review. In analyzing the data, researchers used qualitative analysis techniques with data exposure, data reduction and conclusions. Based on the research that has been done, obtained the result that: 1). To create effective learning PAI teachers formulate a plan that includes: annual programming, semester program, lesson implementation plan, determining minimum graduation criteria conducted at the beginning of each new school year. 2). Organizing learning by PAI teachers are: subject matter, material resources, methods, tools used and strategies selected in delivering the subject matter. 3). Implementation of PAI lessons using the 2013 curriculum. Lessons learned include opening activities, core activities that emphasize exploration of past knowledge of closing activities as feedback and reinforcement of students. 4). In addition to supervision conducted by the Principal, Supervisor of PAI Kemenag Teachers, also held suvervisi meetings every Saturday, monthly supervision meetings, semester meetings and at the end of each semester the head and vice principal evaluate the performance of the teachers for assessment. Teachers who get a good assessment will be rewarded and if the value is low will be given a reprimand both oral and written. 5). In addition to the independent evaluation of the teachers through pre-test, post test, daily test, independent tasks and group assignments, there is also a periodic evaluation of the midsemester exam and the final exam of the semester. 6). The high interest of student learning on PAI lesson is shown by the students' activeness during teaching and learning process because they think the material is very useful in everyday life.